Hepatitis E Virus ORF2 Inhibits RIG-I Mediated Interferon Response - Hingane, Smita; Joshi, Nishant; Surjit, Milan; Ranjith-Kumar, C. T. (Frontiers in Microbiology, 2020)
Understanding the dynamics of host innate immune responses against a pathogen marks the first step towards developing intervention strategies against the pathogen. The cytosolic pattern recognition receptor retinoic acid-inducible gene I (RIG-I) has been shown to be the major innate immune sensor for Hepatitis E virus (HEV). Here, we show that HEV capsid protein (ORF2), a 660 amino acid long protein interferes with the RIG-I signaling. Interestingly, only the full length ORF2 protein but not the 112-608 ORF2 protein inhibited RIG-I dependent interferon response. Both synthetic agonist and virus induced RIG-I activation was modulated by ORF2. Interference of interferon response was confirmed by reporter assays involving different interferon inducible promoters, qRT PCR, ELISA and immunofluorescence microscopy. Neither glycosylation nor dimerization of the ORF2 protein had any effect on the observed inhibition. Further analyses revealed that the ORF2 protein antagonized toll-like receptor (TLR) pathways as well. ORF2 inhibited signaling by RIG-I and TLR adapters, IPS-1, MyD88 and TRIF but was unable to inhibit activation by ectopically expressed IRF3 suggesting that it may be acting at a site upstream of IRF3 and downstream of adapter proteins. Our data uncover a new mechanism by which HEV may interfere with the host antiviral signaling.